2007
DOI: 10.2174/138620707781662817
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Antioxidant Compounds During Sprouting of Brassica oleracea L. var. costata DC

Abstract: Abstract:The changes in antioxidant compounds of Brassica oleracea L. var. costata DC seeds were monitored during the first twelve days of seedling development. Sprouts were screened at time intervals of two days for phenolic compounds and organic acids. The identified phenolic compounds included esters of sinapic acid with glucose, gentiobiose and kaempferol, as well as sinapoylcholine. The organic acids were oxalic, aconitic, citric, pyruvic, malic, shikimic, and fumaric acids. During germination, a depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 28 publications
(59 reference statements)
2
32
0
Order By: Relevance
“…A factorial 3 design in two blocks was used whose factors (and levels) were type of elicitor (sodium selenate, chitosan and methyl jasmonate) and elicitor concentration (10, 50 and 90 µmol L −1 ). The choice of elicitors was based on previous research that showed that chitosan and methyl jasmonate act as signaling molecules, activating metabolic pathways related with plant defense .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A factorial 3 design in two blocks was used whose factors (and levels) were type of elicitor (sodium selenate, chitosan and methyl jasmonate) and elicitor concentration (10, 50 and 90 µmol L −1 ). The choice of elicitors was based on previous research that showed that chitosan and methyl jasmonate act as signaling molecules, activating metabolic pathways related with plant defense .…”
Section: Methodsmentioning
confidence: 99%
“…italica ) are a good source of secondary metabolites exhibiting biological activity (as antioxidants), such as phenolic compounds, vitamins and glucosinolates . The content of these compounds in broccoli depends partly on the development stage of the plant . At early development stages, namely as sprouts of 3–4 days after germination, broccoli presents the highest concentration of bioactive compounds, being 10–100 times higher than ripe broccoli inflorescences, and therefore they are highly appreciated worldwide .…”
Section: Introductionmentioning
confidence: 99%
“…2). The majority of the compounds showed an absorbance maximum at 330 nm, characteristic of hydroxycinnamic acids (Carazzone et al, 2013;Ferreres et al, 2007), the main component of the phenolic profile of other varieties of B. oleracea sprouts and seeds Paja˛k et al, 2014;Sousa et al, 2007). Flavonoids like quercetin and kaempferol derivatives were described as the most common phenolic compounds of mature brassica vegetables.…”
Section: Variation In Contents Of Phenolic Compoundsmentioning
confidence: 99%
“…Flavonoids like quercetin and kaempferol derivatives were described as the most common phenolic compounds of mature brassica vegetables. On the other hand, seeds and sprouts of those vegetables have usually a higher content of hydroxycinnamic acids, especially derivatives of sinapic acid (Ferreres et al, 2006;Ferreres et al, 2007;Pająk et al, 2014;Sousa et al, 2007;Vallejo et al, 2004Vallejo et al, , 2003b. Thus, the hydroxycinnamic acids derivatives were quantified using a sinapic acid standard calibration curve, and the results were presented as mg of hydroxycinnamic acids per kilogram of sprout on a dry weight basis (Fig.…”
Section: Variation In Contents Of Phenolic Compoundsmentioning
confidence: 99%
“…costata ) seeds (13) mature leaves (14) inter-nodal shoots and roots (15, 16). Twelve specific phenolic compounds have been profiled in two- to twelve-day old seedlings possessing both seed-leaves and true-leaves.…”
Section: Introductionmentioning
confidence: 99%